Peran Lembaga Pendidikan Keagamaan Di Masyarakat Dalam Menumbuhkan Perilaku Keagamaan Remaja: Study Kasus Di TPQ Rahmatul Mujtahidin - Aulia Kenes Prameswari; Noor Azida Batubara; Erlis Sulandari; Muhammad Dzulfikar Latif; Nita Kurnia (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the role of religious educational institutions, particularly the Rahmatul Mujtahidin Al-Qur'an Education Park (TPQ), in fostering religious behavior among adolescents. Using a qualitative case study approach, this study was conducted in Selang Cibitung and involved adolescents, administrators, and parents as participants. The results show that TPQ functions as a religious educational institution that can foster religious behavior through a curriculum that emphasizes moral values and religious practices. Positive interactions in the TPQ environment increase adolescents' social attachment and awareness, while parental involvement is an important factor in supporting children's religious education. These findings emphasize the importance of synergy between educational institutions, families, and communities in shaping better adolescent behavior in the modern era. This study also recommends the need for greater attention to institutional support for the development of effective religious education.